2016
DOI: 10.1590/1519-6984.15715
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of nematophagous fungi to antiparasitic drugs: interactions and implications for biological control

Abstract: The fast anthelmintic resistance development has shown a limited efficiency in the control of animal's endoparasitosis and has promoted research using alternative control methods. The use of chemicals in animal anthelmintic treatment, in association with nematophagous fungi used for biological control, is a strategy that has proven to be effective in reducing the nematode population density in farm animals. This study aims to verify the in vitro susceptibility of the nematophagous fungi Arthrobotrys oligospora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
1
19
1
3
Order By: Relevance
“…In vivo assays performed in sheep and buffaloes showed that the activity of D. flagrans chlamydospores is inhibited when used in combination with albendazole, and the fungus is rarely recovered from fecal culture after 48 h following a single dose of albendazole (Sanyal et al 2004). Vieira et al (2017) demonstrated that the minimal inhibitory concentration (MIC) of albendazole against the hyphal growth of D. flagrans is 0Á03 μg ml −1 , which is lower than the EC 50 value of fenbendazole against the spore germination of D. flagrans in this study. In vitro growth assays performed by Singh et al (2010) revealed that albendazole exerts inhibitory effects on two egg-parasitic fungi, Verticillian chlamydosporium and Paecilomyces lilacinus, but V. chlamydosporium is more sensitive to albendazole than P. lilacinus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In vivo assays performed in sheep and buffaloes showed that the activity of D. flagrans chlamydospores is inhibited when used in combination with albendazole, and the fungus is rarely recovered from fecal culture after 48 h following a single dose of albendazole (Sanyal et al 2004). Vieira et al (2017) demonstrated that the minimal inhibitory concentration (MIC) of albendazole against the hyphal growth of D. flagrans is 0Á03 μg ml −1 , which is lower than the EC 50 value of fenbendazole against the spore germination of D. flagrans in this study. In vitro growth assays performed by Singh et al (2010) revealed that albendazole exerts inhibitory effects on two egg-parasitic fungi, Verticillian chlamydosporium and Paecilomyces lilacinus, but V. chlamydosporium is more sensitive to albendazole than P. lilacinus.…”
Section: Resultsmentioning
confidence: 99%
“…Triclabendazole is a widely used benzimidazole fungicide, and it exclusively prevents and cures the diseases caused by Fasciola gigantica and Fasciola hepatica. Regarding an in vitro growth experiment performed by using the microdilution technique, the MIC of triclabendazole against D. flagrans was reported to be 0Á062 μg ml −1 (Vieira et al 2017). This study indicated that EC 50 of triclabendazole against the chlamydospore germination of D. flagrans is 1Á2 μg ml −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vieira et al . (2017) mentioned that antiparasitic compounds have an in vitro inhibitory effect on nematophagous fungi, compromising their activity as biological control agents – something that can be observed in group G7.…”
Section: Resultsmentioning
confidence: 99%